EFFECT OF CYPHENOTHRIN-INDUCED SPLENIC DAMAGE AND HEMATOLOGICAL ALTERATIONS IN MALE WISTAR RATS (RATTUS NORVEGICUS) - B. NEGLUR, SRINIVAS; DAVID, MUNISWAMY (International Journal of Pharmacy and Pharmaceutical Sciences, 2023)
Objective: Cyphenothrin is a major insecticide causing toxicological implications in mammals. Several studies estimated the consequences posed by this insecticide. The present study was designed to investigate the possible pyrethroid effects of cyphenothrin-induced hematological alterations and splenic damage in male Wistar albino rats. Methods: The rats were subjected to 60 d of exposure to a sublethal concentration of cyhenothrin. Hematological analyses revealed alterations in blood indices including red blood cells, white blood cells, hematocrit, hemoglobin, and platelet count. However, increased cyphenothrin level in treated rat groups was significant in the present study. This might be attributed to cyphenothrin enhancing stress of animal physiology. Results: Histological examination of spleen resulted in rarefication of white pulp, damaged marginal zone, decreased periarteriolar lymphoid sheath (PALS) 35.33 mg/Kg BW high dose, and number of lymphoid follicles in the high concentration of cyphenothrin group. However, the treatment of cyphenothrin significantly affected the low-concentration cyphenothrin-treated group more than the high-concentration-treated group 63.6 mg/Kg BW low dose compared to the control. Conclusion: This indicates the effective property of toxicity on the immunomodulatory effects of cyphenothrin. Results of the present study suggest that the Cyphenothrin effect has a potentially key role in hematological and immunomodulatory processes that might be implemented.